Colitis as the Sole Initial Presentation of Chronic Granulomatous Disease: Histopathologic Clues to Diagnosis. Issue 11 (November 2016) - Rosenbaum, Brooke E.; Shenoy, Rivfka; Vuppula, Sharon; Thomas, Kristen; Moy, Libia; Kaul, Aditya
Abstract : Chronic granulomatous disease is a rare, inherited immunodeficiency disorder that reduces the superoxide generation ability of phagocytes, leading to recurrent infections and granulomatous inflammation. We report the case of a previously healthy 3-year-old boy who presented with classic features of Crohn disease. Suspicion from histopathologiclogic assessment allowed early diagnosis and treatment for chronic granulomatous disease before the onset of infections.